Molecular Imaging in Oncology - Schober, Otmar; Riemann, Burkhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The impact of molecular imaging on diagnostics, therapy, and follow-up in oncology is increasing significantly. The process of molecular imaging includes key biotarget identification, design of specific molecular imaging probes, and their preclinical evaluation, e.g., in vivo using small animal studies. A multitude of such innovative molecular imaging probes have already entered clinical diagnostics in oncology. There is no doubt that in future the emphasis will be on multimodality imaging in which morphological, functional, and molecular imaging techniques are combined in a single clinical investigation that will optimize diagnostic processes. This handbook addresses all aspects of molecular imaging in oncology, ranging from basic research to clinical applications in the era of evidence-based medicine. The first section is devoted to technology and probe design, and examines a variety of PET and SPECT tracers as well as multimodality probes. Preclinical studies are then discussed in detail, with particular attention to multimodality imaging. In the third section, diverse clinical applications are presented, and the book closes by looking at future challenges. This handbook will be of value to all who are interested in the revolution in diagnostic oncology that is being brought about by molecular imaging.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Oncology; Medicine & Public Health; Oncology; Diagnostic Radiology; Nuclear Medicine; Imaging / Radiology